2010
DOI: 10.1002/app.31824
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and sorption studies of β‐cyclodextrin/epichlorohydrin copolymers

Abstract: b-Cyclodextrin (b-CD) copolymer materials were synthesized by reacting different mole ratios (1 : 15, 1 : 25 and 1 : 35) of b-CD with epichlorohydrin (EP). The products were characterized using N 2 porosimetry, Fourier Transform Infrared spectroscopy, 13 C CP-MAS NMR spectroscopy, thermogravimetry analysis, elemental (C and H) analysis, and scanning electron microscopy. The sorption properties in aqueous solution were studied using p-nitrophenol (PNP) with UV-Vis spectrophotometry. Sorption isotherms were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 29 publications
7
40
0
Order By: Relevance
“…The shift in temperature stability of the copolymers is related to the change in heat capacity, H-bonding effects, and the amorphous character of the copolymers as the linker content increases. Similar TGA results were reported for urethane- [31], epichlorohydrin- [34], and polyester-based copolymers [19] containing b-CD.…”
Section: Physicochemical Characterization Of Copolymerssupporting
confidence: 89%
“…The shift in temperature stability of the copolymers is related to the change in heat capacity, H-bonding effects, and the amorphous character of the copolymers as the linker content increases. Similar TGA results were reported for urethane- [31], epichlorohydrin- [34], and polyester-based copolymers [19] containing b-CD.…”
Section: Physicochemical Characterization Of Copolymerssupporting
confidence: 89%
“…Scheme 2) [35]. Previous sorption studies have hypothesized the occurrence of inclusion binding and non-inclusion adsorption of dyes onto the copolymer framework [30,46]. Therefore, SA estimates of CD-based polymers using the dye-based method are subject to error when an inappropriate isotherm (e.g., Langmuir) is applied to heterogeneous sorption (i.e., multi-site binding) phenomena.…”
Section: Dye Sorption Resultsmentioning
confidence: 98%
“…The greater SA estimates derived from the dye-based method are attributed to framework structural changes of the copolymer in aqueous solution despite the relative insolubility of the copolymers in water. In a previous study, the occurrence of swelling for CD-based copolymers was reported [6,7,30,36,37]. Quantitative estimates of the swelling were determined from water uptake measurements for a urethane-methacrylate b-CD copolymer that ranged from 34.2% to 50.2% [38].…”
Section: Dye Sorption Resultsmentioning
confidence: 99%
See 2 more Smart Citations